Model Literasi Media Berbasis Kearifan Lokal pada Suku Dayak Tunjung dan Dayak Benuaq di Kutai Barat - Fitryarini, Inda; Juwita, Rina; Purwaningsih, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2014)
This study begins from a simple question on how Dayak Benuaq and Dayak Tunjung/Tonyoii people (individually and collectively) are able to maintain their local wisdom and local culture in the midst of the ambush of mass media exposure and then acknowledged as the Dayak tribes who are still âBeradat (Wellmannered)â. Their local wisdom which is still maintained were able to counteract the negative effects of mass media exposure so it can be used as a model of literacy media, either through media literacy education or media literacy movement. This study used a qualitative explanatory method and used a communication ethnographic approach in field. Primary data was collected through interview and observations of some Dayak Benuaq and Dayak Tunjung people, including some community leaders and local government officials that found with the snowball sampling technique. The results showed that, first, public awareness through the local wisdom lense in media literacy has not been able yet to maximize their own potential due to society passivity as media users, as well as a lack of support from the government to create a media savvy society. Second, the model used within both tribes is known as Protectionist Model based on their local wisdom which includes four kinds of elements, which are; the ability to access, to analyse, to evaluate, and to create content.